The luminosity - spectral index dependence of the X-ray bright Seyfert galaxies - Sadova, V.A.; Tugay, A.V. (Advances in Astronomy and Space Physics, 2015)
X-ray luminosities and spectral indices of 97 bright Seyfert 1 (Sy1) galaxies from the XMM-Newton archive are analysed in this article. Distribution of these values is random, so we conclude that the model of emission should be at least two-parametric. Within the framework of the merging model of active galactic nuclei (AGN), the relation between black hole mass, stage of merging and observable X-ray parameters is roposed.